Questione dignità - Colaianni, Nicola (Dignità umana, 2024)
An unresolved question emerges from the numerous constitutional or international texts that contain the reference to dignity: is homo dignus man as such, in his kind, or, as the Italian Constitution affirmed, a person in his/her community? This results in two opposing conceptions of dignity: objective – based on guarantees and limitations of human rights – and subjective – which is linked to the self-determination of each human person. That reflect in the field of bioethics, where it is common to distinguish two systems of thoughts: Christian bioethics and secular bioethics. In this essay the two paradigms are tested with constitutional jurisprudences related to end-of-life and medically assisted procreation. The result is a tendency to bring out the dimension of dignity as a source of some fundamental rights, such those related to as self-determination, in balance with each other rights, such as those referring the inviolability of human life. In general, the notion of dignity cannot be divorced from that of obligation. As such, an a priori notion of dignity must be tested in the light of the notion of cultural-religious pluralism.